PELATIHAN EMOTION COACHING UNTUK MENINGKATKAN KETRAMPILAN GURU MERESPON EMOSI ANAK USIA DINI - Astinah Astinah; Hepi Wahyuningsih; Ratna Syifa'a Rachmahana (JIP (Jurnal Intervensi Psikologi), 2019)
This research aims to observe how the emotion coaching training improve the skill of teachers on Education for Early-Age Children (known as PAUD). It uses the design of nonrandomized pretest-posttest control group design. Twelve teachers of PAUD were involved as the participants in this research and they were divided into two groups: 6 of those 12 teachers included in experimental and control group. The measurement tools used in this research were the scale of the skill of teacher response and observation on checklist behavior made by the researcher based upon the theory of Swartz and Mcelwain (2012).. The test of hypothesis used the Friedman analysis. The results of the research showed that the training of emotion coaching can improve the skill of teachers in responding the emotion of early age children before and after giving the training to the experiment group at (p = 0.002 where p< 0.05).